Improvement of conduction band offset and efficiency of Cu2ZnSn(S, Se)4 thin film solar cells by Cd alloying. (December 2020) - Sun, Luanhong; Shen, Honglie; Huang, Hulin; Raza, Adil; Zhao, Qichen; Hu, Dongli
Abstract: In this study, a novel strategy for achieving flexible Cd-alloyed Cu2 ZnSn(S, Se)4 thin film solar cells is demonstrated by evaporating a CdS layer with different thickness on Cu2 ZnSnS4 precursor followed by selenization process. Improved crystalline quality with enlarged grain size was observed through XRD, Raman and SEM measurements. For Cu2 Cdx Zn1-x Sn(S, Se)4 thin film with 50 nm CdS alloying layer, a smallest conduction band offset with −0.20 eV was obtained, which relieved the band mismatching problem between CZTSSe and buffer CdS. Besides, the contact angle of absorber showed a clear difference after Cd alloying, decreasing from 67.8° to 41.2° with the gradual increase in x. Finally, the best device performance benefited from the optimal 50 nm CdS alloying layer, featuring a PCE of 4.01%, Voc of 346.30 mV, Jsc of 24.23 mA/cm −2 and FF of 47.71%, which showed a PCE increase of 1.73% than that without Cd alloying.